Decision Making and Business Ethics: The Implications of Using Image Theory in Preference to Rational Choice - Morrell, Kevin (Journal of business ethics, 2004)
The study of decision making has multiple implications for business ethics. This paper outlines some commonly used frameworks for understanding choice in business. It characterises the dominant model for business decision making as rational choice theory (RCT) and contrasts this with a more recent, naturalistic theory of decision-making, image theory. The implications of using RCT and image theory to model decision making are discussed with reference to three ethical systems. RCT is shown to be consistent with Utilitarian ethics, but not with Kantian or Virtue-based ethics. Image theory is shown to be consistent with each. The paper identifies a number of implications following from this analysis.